“Bandido bom é bandido morto”? análise do discurso crítica aplicada a reações sobre chacinas publicadas pelo jornal Diário Online em sua página no Facebook - LEITE, Vivianne Carolina Oliveira de Sousa (Universidade Federal do Pará, 2021)
This paper presents the results of research on the reactions of Internet users to the news of violence on social networks, in particular those related to the massacres of Belém (2014), Tapanã (2018) and Guamá (2019) that took place in the city of Belém and published by the newspaper Diário Online (DOL) on its Facebook page. Through it, we seek to identify patterns of reaction to headlines; analyze the intentionality of the headlines in the Diário Online newspaper; and interpret the social meanings around reactions of users of social networks on the phenomenon of urban violence in the city of Belém. To achieve these goals, we used Critical Discourse Analysis as a methodology for analyzing Internet users' reactions to the headlines about massacres published by the Diário Online newspaper on their Facebook page between the years 2016, 2017, 2018, and 2019.